An integrative review to identify evidence of nurse practitioner‐led changes to health‐care delivery and the outcomes of such changes. Issue 6 (8th December 2020) - Ryder, Mary; Jacob, Elisabeth; Hendricks, Joyce
Abstract: Aims: This study aimed to identify evidence of nurse practitioner‐led changes to health‐care delivery and the outcomes of such changes. Background: Changing health‐care delivery is synonymous with the nurse practitioner role. The literature is critical of the lack of research by nurse practitioners, reporting the effects of a change to health‐care delivery. Design: This study used a systematic integrative review by using Torraco's approach. Data sources: Databases Cumulative Index to Nursing and Allied Health Literature, MEDLINE, Web of Science and SCOPUS were searched for peer‐reviewed publications from 2000 to 2019. Review Methods: A systematic approach was used to screen and analyse the literature. Inclusion/exclusion criteria were applied, and quality appraisal was undertaken by two reviewers. Results: Eighteen articles were selected. The research projects were across the community and acute care settings. Research methodologies varied including preintervention and postintervention studies, evaluation of quality improvement projects, randomized controlled trial and descriptive studies. Multiple data collection tools were used. Two major themes were identified including evidence‐based practice champions and improved patient outcomes. Conclusion: The nurse practitioner role is pertinent toward improving evidence‐based practice in clinical settings. Positive patient outcomes and praise for clinical leadership are evident in the literature. Research by nurse practitioners to date has focused on individual services. SUMMARY STATEMENT: What is already known about this topic? Nurse practitioners are responsible for transforming health‐care delivery. The leadership role of nurse practitioners includes evaluation of the quality of patient care. Research related to the effects of such transformation is lacking. What this paper adds? The effect of nurse practitioner‐led health‐care transformation was measured using a variety of evidence‐based measurement tools to determine patient outcomes. The literature identified that nurse practitioners are evidence‐based practice champions. Nurse practitioner health‐care transformation interventions have improved patient outcomes. The implications of this paper: The importance of measuring the effects of changes to health‐care delivery is highlighted as they reflect the nursing profession's contribution to the health‐care reform agenda. The paper has identified a gap in knowledge related to nurse practitioner perceptions of their leadership and research role. This research identified that nurse practitioner preparedness for research requires further examination.